BRINGING STUDENTS’ HOME AND FOREIGN CULTURE INTO LANGUAGE CLASSROOM: UNVEILING INDONESIAN EFL TEACHERS’ BELIEF AND PRACTICES - Ulil Fitriyah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
In the 21st century teaching, the function of English language classroom is not limited merely to preparing students to be able to communicate with native English language users. But, it is widely to prepare them to be successfully engaged with a global milieu in intercultural settings. However, this situation remains challenging for EFL teachers worldwide. It was evidenced by many scholars that teachers’ positive perception toward interculturality in language teaching did not concurrently lead to the practice of language pedagogy in the classroom. This paper attempts to explore how Islamic Indonesian teachers perceive intercultural competence in the language classroom as well as how it is reflected in their teaching practices. By using electronic questionnaire, data were collected from 20 lecturers teaching Intensive English Course offered in the first semester of new college students majoring English. The results of the study indicated a strong positive belief toward intercultural competence, yet it is not congruent in its pedagogical activity in the classroom. Following this, further research possibility is also discussed in last section of this paper.